Physical activity and Academic-Achievement of Medical Students: An Analytic Cross-sectional Study in Karachi - Naila Baig; Mirza Altamish Muhammad Baig; Khubaib Muhammad Shamim Meah (Shalamar Medical & Dental College, Lahore, Pakistan, 2024)
Background: Physical inactivity is prevalent among medical students, with inconsistent academic scores. Physical activity enhances cognition and performance and improves academic achievement. Objective: To determine how medical students' physical activity and associated factors influence academic achievement.  Methods: Using convenience sampling, this analytic cross-sectional study involved Dow International Medical College MBBS students of 1st year and 2nd year, to fill the International-Physical-Activity-Questionnaire-S7S. This estimated day-to-day physical activity/week, metabolic equivalent task (MET)-minutes/week, as physical-activity-scores. Annual examination percentage scores were used as academic achievement scores. Statistical significance was determined at p<0.05. Results: The response rate was 229/307 (74.6%). Median physical activity scores and academic achievement scores were 1188.00 MET-minutes/week and 59.28%. Males were more physically active (p=0.001) despite the female predominance of 54.15%, and 2nd-year students (n=113), had significantly higher academic achievement scores (p=0.001). Ethnicity, physical limitation, and smoking status had insignificant effects on academic achievement. There was no statistically-significant difference in physical-activity-scores and academic-achievement-scores as per different age-groups (p=0.933, ηp2=0.003 and, p=0.276, ηp2=0.011), and BMI-groups (p=0.218, ηp2=0.021 and (p=0.044, ηp2=0.039). There was a tendency for between-the-group variance (p=0.04) in the "normal-weight" and "obese" BMI groups.   Physical-activity-scores and academic-achievement-scores showed no correlation (rs=0.035, p=0.597), and were independent of sitting hours/day (rs=0.043, p=0.558 and rs=0.039, p=0.603), sleep-hours/day (rs=0.077, p=0.223 and rs=0.001, p=0.984), and study hours/day (rs=0.040, p=0.556 and rs=0.091, p=0.181). Physical activity categories and academic achievement groups appeared independent of each other with no effect. (p=0.363, φc=0.097).   Conclusion: Physical activity has no effect on academic achievement of undergraduate medical students. Male student were physically more active but there was no association of gender with academic achievement. Key Words: Physical Activity, Academic Achievement, Academic Scores, Medical Students